2007
DOI: 10.1210/en.2007-1263
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Perinatal Undernutrition Drastically Reduces Postnatal Leptin Surge and Affects the Development of Arcuate Nucleus Proopiomelanocortin Neurons in Neonatal Male Rat Pups

Abstract: A growing body of evidence suggests that maternal undernutrition sensitizes the offspring to the development of energy balance metabolic disorders such as type 2 diabetes, dyslipidemia, and obesity. The present study aimed at examining the impact of maternal undernutrition on leptin plasma levels in newborn male rats and on the arcuate nucleus proopiomelanocortin (POMC) and neuropeptide Y (NPY) neurons that are major leptin targets. Using a model of perinatal maternal 50% food-restricted diet (FR50) in the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
238
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(253 citation statements)
references
References 30 publications
12
238
0
3
Order By: Relevance
“…We found that the leptin surge was much shorter in the undernourished rats and did not peak at 10 days. Comparable results have been reported in other models of early nutrition imbalances (32,33). These deficiencies could reflect decreased milk or leptin production, or impaired absorption.…”
Section: Discussionsupporting
confidence: 65%
“…We found that the leptin surge was much shorter in the undernourished rats and did not peak at 10 days. Comparable results have been reported in other models of early nutrition imbalances (32,33). These deficiencies could reflect decreased milk or leptin production, or impaired absorption.…”
Section: Discussionsupporting
confidence: 65%
“…Many imprinted genes show high expression in key components of the hypothalamo-pituitary axis (our observations; [74,85]) and although genetic mouse models of altered dosage at the Dlk1-Dio3, Peg3 and Gnas loci show altered ''set points'' of metabolic axes there is, to our knowledge, currently no data linking changes in the early life environment with changes in the central nervous system expression of imprinted genes [86][87][88][89].…”
Section: Imprinted Genes In Brain Development and The Central Controlmentioning
confidence: 99%
“…Thirdly, post-natal leptin surge was modified following maternal nutrition manipulation (i.e. suppressed, Delahaye et al (2008)). Finally, leptin activated adipogenesis by promoting differentiation of preadipocytes (Bol et al 2009) whereas it showed antilipogenic effects on mature adipocytes (Huan et al 2003).…”
Section: Circulating Factorsmentioning
confidence: 99%